Preoperative Anxiety in Adult Female Tooth Extraction Patients: Kecemasan Praoperasi pada Pasien Perempuan Dewasa yang Akan Melakukan Ekstraksi Gigi - Nuryono, Stevia Vebianti; Ansyah, Eko Hardi (Indonesian Journal on Health Science and Medicine, 2025)
General background: Anxiety prior to dental procedures remains a common psychological challenge across patient populations. Specific background: Despite advancements in dental technology and treatment approaches, many adult patients, particularly women, continue to experience significant preoperative anxiety before tooth extraction. Knowledge gap: Limited qualitative research explores the lived experiences and underlying factors contributing to such anxiety in adult female patients within local clinical contexts. Aims: This study seeks to describe the manifestations of preoperative anxiety in adult female tooth extraction patients and to identify the psychological and experiential factors that contribute to it. Results: Using a phenomenological qualitative method with purposive sampling of two adult female patients at Dr. Ny Ade’s dental practice, findings revealed shared experiences of fear triggered by dental instruments, nervousness, and uneasiness before extraction. Contributing factors included past negative personal experiences, observing painful procedures in others during childhood, and irrational anticipations of excessive pain. Novelty: This study provides in-depth qualitative insights into how early dental experiences and cognitive perceptions shape preoperative anxiety among adult women. Implications: The findings underscore the importance of tailored communication and supportive strategies by dental practitioners to mitigate anxiety, improve patient trust, and optimize treatment outcomes. Highlights: Anxiety in adult women is shaped by past and observed painful experiences. Fear is intensified by dental instruments and irrational anticipation of pain. Findings emphasize the need for patient-centered anxiety management in dentistry. Keywords: Preoperative Anxiety, Tooth Extraction, Adult Female Patients, Dental Fear, Phenomenology